Improved Survival and Neurological Outcomes after Cardiopulmonary Resuscitation in Toll-like Receptor 4-mutant Mice - Xu, Li; Zhang, Qing; Zhang, Qing-Song; Li, Qian; Han, Ji-Yuan; Sun, Peng (Chinese medical journal, 2015)
Background：Toll-like receptor 4 （TLR4） is a crucial receptor in the innate immune system and noninfectious immune responses.It has been reported that TLR4 participates in the pathological course of ischemia/reperfusion （I/R） injury.However,the role of TLR4 in the process of I/R injury after cardiac arrest （CA） and cardiopulmonary resuscitation （CPR） is still unknown.In this study,we investigated the effects of TLR4 mutation on survival and neurological outcome in a mouse model of CA/CPR.Methods：A model of potassium-induced CA was performed on TLR4-mutant mice （C3H/HeJ） and wild-type mice （C3H/HeN）.After 3 min of untreated CA,resuscitation was attempted with chest compression,ventilation,and intravenous epinephrine.Behavioral tests were performed on mice on day 3 after CPR.The morphological changes in hippocampal neurons were assessed by light and electron microscopy.Expressions of TLR4 and intercellular adhesion molecule-1 （ICAM-l） were detected by Western blot.Levels of tumor necrosis factor-α （TNF-α） and myeloperoxidase （MPO） were measured with enzyme-linked immunosorbent assay （ELISA）.Results：On day 3 after resuscitation the overall mortality was 33.33％ in C3H/HeJ group compared with 53.33％ in C3H/HeN group （P ＜ 0.05）.And there was much higher central tendency in C3H/HeJ group than C3H/HeN group during open field test （P ＜ 0.05）.Meanwhile,the percentage of nonviable neurons was 2 1.16％ in C3 H/HeJ group compared with 53.11％ in C3H/HeN group （P ＜ 0.05）.And there were significantly lower levels ofhippocampal TNF-α and MPO in C3H/HeJ mice （TNF-α：6.85±1.19 ng/mL,MPO：0.33±0.11 U/g） than C3 H/HeN mice （TNF-α：11.36±2.12 ng/mL,MPO：0.54±0.17 U/g） （all P ＜ 0.01）.CPR also significantly increased the expressions of TLR4 and ICAM-1 in C3H/HeN group.However,the expression ofICAM-l was much lower in C3H/HeJ group than in C3H/HeN group after CPR （P ＜ 0.01）.Conclusion：TLR4 signaling is involved in brain damage and in inflammation triggered by CA/CPR.